Renal Response Criteria for Clinical Trials in Amyloid Light Chain Amyloidosis - Nelson Leung; Raymond Comenzo; Julian Gillmore; Andrea Havasi; Efstathios Kastritis; Spencer Guthrie; James Signorovitch; Dena Heath; Isabelle Lousada; Yolanda Barbachano; Krishna Prasad; Kimberly Smith (Kidney International Reports)
Immunoglobin light chain (AL) amyloidosis is a rare disease characterized by organ deposition of amyloid fibrils, most commonly in the heart and kidney. Disease heterogeneity necessitates organ-specific assessment to determine prognosis and response or progression. To facilitate development of new therapies, the Amyloidosis Forum (a public-private partnership between the US Food and Drug Administration and the nonprofit Amyloidosis Research Consortium) held a series of meetings and formed multiple working groups to identify clinical trial end points and analytic strategies. This report summarizes the recommendations of Renal Working Group. Estimated glomerular filtration rate (eGFR) and proteinuria were selected to evaluate eligibility, response, and/or progression in the context of investigational clinical trials for patients with AL amyloidosis. Accurate response assessments at the earliest possible time point were emphasized. The context of use, specific patient population, and the investigational therapeutic mechanism should ultimately drive selection of appropriate end points to evaluate renal response/progression in AL amyloidosis clinical trials.